Congenital Cerebellar Vermis Aplasia Associated with Hydrocephalus in a Foal - Moreira, Matheus V. L.; Kassem, Iolanda G.; Palhares, Maristela S.; Maranhão, Renata P. A.; Ecco, Roselene (Brazilian Journal of Veterinary Pathology, 2015)
A 2-day-old Mangalarga Marchador colt was presented with clinical signs of severe mental depression, unable to stand, and lacking a suckling reflex. Despite intensive medical care, there was no improvement and the colt died 30 hours later. Gross lesions were characterized by aplasia of the cerebellar vermis, cystic dilatation of the fourth ventricle, communicant hydrocephalus involving all ventricles and villous hyperplasia of the choroid plexus in the fourth ventricle. The cerebral parenchyma adjacent to lateral ventricles was markedly reduced. In addition, there was aspiration pneumonia. Aplasia of the cerebellar vermis and cystic dilatation of the fourth ventricle could be compared to the Dandy-Walker-syndrome (DWS). Nevertheless, congenital cerebellar anomalies combined with villous hyperplasia of the choroid plexus in the fourth ventricle and hydrocephalus are describing for the first time in animals, alerting clinicians and pathologists for future investigations about the incidence and etiology of the condition.